2013
DOI: 10.1093/intqhc/mzt059
|View full text |Cite
|
Sign up to set email alerts
|

Health services accreditation: what is the evidence that the benefits justify the costs?

Abstract: The lack of formal economic appraisal makes it difficult to evaluate accreditation in comparison to other methods to improve patient safety and quality of care. The lack of a clear relationship between accreditation and the outcomes measured in the benefit studies makes it difficult to design and conduct such appraisals without a more robust and explicit understanding of the costs and benefits involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
1
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 29 publications
0
47
1
7
Order By: Relevance
“…However, we are not aware of any formal economic evaluation in the literature, which is confirmed by Mumford et al [6] who conducted a systematic review on the use of economic evaluation techniques in connection with health services accreditation. Nevertheless, there exist different attempts to analyze the impact of hospital accreditation that are mainly based on meta-analyses, single cost or benefit studies.…”
Section: Related Literaturementioning
confidence: 84%
See 2 more Smart Citations
“…However, we are not aware of any formal economic evaluation in the literature, which is confirmed by Mumford et al [6] who conducted a systematic review on the use of economic evaluation techniques in connection with health services accreditation. Nevertheless, there exist different attempts to analyze the impact of hospital accreditation that are mainly based on meta-analyses, single cost or benefit studies.…”
Section: Related Literaturementioning
confidence: 84%
“…The order of the other benefits is: [3] fulfillment of the hospital vision, [4] improved image upon stakeholders (patients, suppliers etc. ), [5] improved image in policy, [6] quality dashboard, [7] preparation of centralized quality documents, and [8] avoidance of liability cases.…”
Section: Improvement Of the Meetings Of The Complication Boardmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of matters previously explained, we can mention that the benefits of accreditation deserve to be continuously problematized, or further clarified, if they are indeed the result of this system, since the certification process is widely known to be expensive 16 . As a result, some Australian researchers have concluded that there is an imminent need to foster new studies oriented toward the evaluation of costs in relation to the benefits of accreditation, which implies in a formal economic assessment of the certification process in the light of its little explored benefits 17 . In the explanation of this category, quality managers considered that accreditation represents a worthwhile system for management and quality of hospital care.…”
Section: So All That We Have Developed [In the Accreditation Processmentioning
confidence: 99%
“…In the case of credit rating agencies, recent research see their foundation as a necessary consequence of the expansion of credit markets and the need of investors to manage increasing uncertainty (Alcubilla et al 2012;Langohr and Langohr 2010;Carruthers 2013;Olegario 2003). In both cases, only a few agencies and their ratings came to dominate each field, even though there was not a lot of widespread evidence for their value and contribution to improving the performance of the regulated organizations (Carruthers 2013;Mumford et al 2013). Furthermore, state involvement through the use of these agencies' ratings for regulatory purposes was a very important factor in shaping both settlements.…”
Section: Accrediting Agencies For Healthcare Organizationsmentioning
confidence: 99%